The Role of Educational Psychology in Facing Educational Challenges in the Digital Era - Anindya Rizka Ayunda; Meisya Nur Azizah; Yuni Kartika; Tarsono (al-Afkar, Journal For Islamic Studies, 2026)
Education in the current digital era presents a new challenge for parents, students, and the community. Although technology brings many benefits, it also presents serious problems due to educators' unpreparedness, students' unequal use of technology, and the need to integrate educational psychology with modern technology. This study aims to identify the main challenges in digital era education and explain the role of educational psychology in addressing them. The research method uses a qualitative approach through a literature review, analyzing literature related to the industrial revolution 1.0 to the disruptive era 5.0, as well as the role of technology in education. The results show that the main challenges include the lack of educator competence in technology, students' dependence on social media and games, and minimal infrastructure support. Educational psychology plays a crucial role in guiding educators and students to adapt to technology productively, creating an inclusive, innovative, and sustainable education.